PERAN DINAS PARIWISATA, PEMUDA DAN OLAHRAGA DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN BONE BOLANGO - Hasan, Kurniadi; Otto, Nur Mutmaina; Mokodongan, Regi; Yusuf, Novita; Abas, Sintia Rahmatia (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to determine the role of the Tourism, Youth and Sports Office in developing the tourism sector in Bone Bolango Regency, with a special focus on tourist destinations in Bone Bolango Regency. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, direct interviews with informants and documentation. Data analysis is carried out through the stages of data reduction, data presentation and drawing conclusions. The results of the study indicate that the role of the Tourism Office in developing tourism in Bone Bolango has not been running optimally. Although several aspects of development have been implemented well, in its implementation it still faces obstacles, especially in terms of budget limitations. In addition, several other obstacles include the lack of supporting facilities and infrastructure in most tourist destinations, as well as tourism promotion efforts that are still limited to social media, not utilizing broader and more effective promotional strategies. In terms of accessibility to tourist destinations, it is quite good, as well as the potential for local products which are quite large, but have not been fully supported by adequate infrastructure.